The Effectiveness of “Emolabeling” to Promote Healthy Food Choices in Children Preschool Through 5th Grade - Privitera, Gregory J.; Phillips, Taylor E.; Misenheimer, Melissa; Paque, Robert (International Journal of Child Health and Nutrition, 2014)
Obesity has become a growing global concern. Evidence indicates that ecological factors are most predictive of obesity among children, and that a new strategy, referred to as emolabeling, may effectively address ecological factors, although the extent to which it can influence food choice is not yet known, but tested here. Specifically, we tested the hypothesis that children aged 3 to 11 years will use emolabels, or emotional correlates of health (i.e. healthy-happy, unhealthy-sad), to make healthy food choices. A cross-sectional design was used with two phases. In Phase 1, children were taught how to use emolabels with a “faces of health” lesson. In Phase 2, children made choices between containers that were laid out on a large table in pairs and varied by taste (tastes good, no information), social norms (popular, not popular), branding (image of a minion, no image), or preference (told what food was in each container). A control pair was labeled with only emoticons. The order and presentation of the containers were counterbalanced for each variation. Results showed that a significant proportion of children in the pre-literacy and the early literacy grades used emoticons to specifically make healthy food choices in each variation (p < .05 for all tests), except when children were told what foods were in the containers. In all, emolabeling effectively influenced food choices for healthy foods among children aged 3 to 11 years, more so than labeling for taste, social norms, and branding, but not preference.